2017
DOI: 10.1158/1078-0432.ccr-16-0594
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Del17p CLL Depends on Genomic Complexity and Somatic Mutation

Abstract: Purpose Chronic lymphocytic leukemia (CLL) with 17p deletion typically progresses quickly and is refractory to most conventional therapies. However, some del(17p) patients do not progress for years, suggesting that del(17p) is not the only driving event in CLL progression. We hypothesize that other concomitant genetic abnormalities underlie the clinical heterogeneity of del(17p) CLL. Experimental Design We profiled the somatic mutations and copy number alterations (CNA) in a large group of del(17p) CLL as we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 50 publications
(83 reference statements)
10
68
4
1
Order By: Relevance
“…Woyach et al (2014) described characteristic resistance mutations arising during ibrutinib treatment among patients with CLL progression, and a subsequent report detailing outcomes from a large single‐institution cohort of ibrutinib‐treated CLL patients found that the presence of a complex karyotype rather than del(17p) was associated with a 4‐fold increase in the risk for discontinuation due to disease progression during ibrutinib treatment (Maddocks et al , 2015). Findings from subsequent studies also suggest that cytogenetic complexity is a prognostic marker of poorer outcomes in the presence or absence of del(17p) (Thompson et al , 2015; Yu et al , 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Woyach et al (2014) described characteristic resistance mutations arising during ibrutinib treatment among patients with CLL progression, and a subsequent report detailing outcomes from a large single‐institution cohort of ibrutinib‐treated CLL patients found that the presence of a complex karyotype rather than del(17p) was associated with a 4‐fold increase in the risk for discontinuation due to disease progression during ibrutinib treatment (Maddocks et al , 2015). Findings from subsequent studies also suggest that cytogenetic complexity is a prognostic marker of poorer outcomes in the presence or absence of del(17p) (Thompson et al , 2015; Yu et al , 2017). …”
Section: Discussionmentioning
confidence: 99%
“…However, a recent large study of 69 patients with del(17p) and CLL identified 3p, 4p, 8p, and 9p as recurrent events significantly associated with del(17p) but not del(18p). 41 Thus, the possibility remains that del(18p) does not happen by chance in the setting of ibrutinib treatment, and it may cooperate with TP53 in conferring refractoriness to prior therapies and in increasing risk of relapse during ibrutinib treatment. In a way, what we observed here could be similar to the association between del(17p)/TP53 mutations, complex cytogenetics, and enriched 5q/7q loss in the setting of acute myeloid leukemia and myelodysplastic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…RPS15 mutations are frequently associated with TP53 mutations. Mutant RPS15 p.G132A experimentally increased TP53 degradation through increased ubiquitination, as compared with wild‐type RPS15 (Ljungstrom et al , ; Yu et al , ).…”
Section: Cell Cycle Apoptosis and Dna Damage And Synthesismentioning
confidence: 99%
“…Chromosome 2p gain is however associated with advance disease and treatment resistance (Chapiro et al, 2010). A complex karyotype (defined as composed of 3 or more abnormalities) has been associated with an unfavourable prognosis, short time to treatment and poor response to treatment Herling et al, 2016;Yu et al, 2016). Almost 20% of cases with no aberration detected by the standard FISH panels ("normal" FISH) were reported to carry complex karyotypes (Rigolin et al, 2012).…”
Section: Cytogenetics and Copy Number Alterationsmentioning
confidence: 99%